Phylogeny and classification of armored scale insects (Hemiptera: Coccomorpha: Diaspididae) - Normark, Benjamin B.; Okusu, Akiko; Morse, Geoffrey E.; Peterson, Daniel A.; Itioka, Takao; Schneider, Scott A. (Zootaxa, 2019)
Armored scale insects (Hemiptera: Coccomorpha: Diaspididae) are major economic pests and are among the world’s most invasive species. Here we describe a system of specimen and identification management that establishes a basis for well-vouchered molecular identification. We also present an expanded Bayesian phylogenetic analysis based on concatenated fragments of 4 genetic loci: the large ribosomal subunit (28S), elongation factor-1 alpha (EF-1α), cytochrome oxidase I and II (COI‒II), and the small ribosomal subunit (16S) of the primary endosymbiont, Uzinura diaspidicola (Bacteroidetes: Flavobacteriales). Our sample includes 1,389 individuals, representing 11 outgroup species and at least 311 described and 61 undescribed diaspidid species. The results broadly support Takagi’s 2002 classification but indicate that some revisions are needed. We propose a revised classification recognizing 4 subfamilies: Ancepaspidinae Borchsenius, new rank, Furcaspidinae Balachowsky, new rank, Diaspidinae Targioni Tozzetti, and Aspidiotinae Westwood. Within Aspidiotinae, in addition to the existing tribes Aspidiotini Westwood, Parlatoriini Leonardi, Odonaspidini Ferris, Leucaspidini Atkinson, and Smilacicolini Takagi, we recognize as tribes Gymnaspidini Balachowsky, new rank, and Aonidiini Balachowsky, new rank. Within Diaspidinae we recognize the 2 tribes Lepidosaphidini Shimer and Diaspidini Targioni Tozzetti, and within Diaspidini we recognize three subtribes: Diaspidina Targioni Tozzetti, Fioriniina Leonardi, and Chionaspidina Brues & Melander. We regard Kuwanaspidina Borchsenius as a junior synonym of Fioriniina, Thysanaspidini Takagi as a junior synonym of Leucaspidini, and Protodiaspidina Takagi and Ulucoccinae Takagi as junior synonyms of Chionaspidina. To clarify the composition of the higher taxa we describe 2 new genera for Australian species heretofore misplaced in the genus Ancepaspis Ferris: Brimblecombia Normark (Aonidiini) and Hendersonaspis Normark (Leucaspidini). We also propose many additional minor modifications to the taxonomy of Diaspididae, including the following new combinations, revived combinations, and replacement names: Aonidia edgerleyi (Mamet), new combination (from Bigymnaspis Balachowsky); Aonidomytilus espinosai Porter, revived combination (from Porterinaspis González); Aspidiotus badius (Brain), new combination (this and the next 5 Aspidiotus species all from Aonidia Targioni Tozzetti); Aspidiotus biafrae (Lindinger), new combination; Aspidiotus chaetachmeae (Brain), new combination; Aspidiotus laticornis (Balachowsky), new combination; Aspidiotus rhusae (Brain), new combination; Aspidiotus sclerosus (Munting), new combination; Brimblecombia asperata (Brimblecombe), new combination (this and the next 5 Brimblecombia species all from Ancepaspis); Brimblecombia longicauda (Brimblecombe), new combination; Brimblecombia magnicauda (Brimblecombe), new combination; Brimblecombia reticulata (Brimblecombe), new combination; Brimblecombia rotundicauda (Brimblecombe), new combination; Brimblecombia striata (Brimblecombe), new combination; Cooleyaspis pseudomorpha (Leonardi), new combination (from Dinaspis Leonardi); Cupidaspis wilkeyi (Howell & Tippins), new combination (from Paracupidaspis Howell & Tippins); Cupressaspis isfarensis Borchsenius, revived combination (this species, the next 2 species in Cupressaspis Borchsenius, revived genus, and the next 9 species in Diaspidiotus Cockerell all from Aonidia); Cupressaspis mediterranea (Lindinger), revived combination; Cupressaspis relicta (Balachowsky), new combination; Diaspidiotus atlanticus (Ferris), new combination; Diaspidiotus marginalis (Brain), new combination; Diaspidiotus maroccanus (Balachowsky), new combination; Diaspidiotus mesembryanthemae (Brain), new combination; Diaspidiotus opertus (De Lotto), new combination; Diaspidiotus shastae (Coleman), new combination; Diaspidiotus simplex (Leonardi), new combination; Diaspidiotus visci (Hall), new combination; Diaspidiotus yomae (Munting), new combination; Diaspis arundinariae (Tippins & Howell), new combination (from Geodiaspis Tippins & Howell); Duplachionaspis arecibo (Howell), new combination (this and the next 10 Duplachionaspis MacGillivray species all from Haliaspis Takagi); Duplachionaspis asymmetrica Ferris, revived combination; Duplachionaspis distichlii (Ferris), revived combination; Duplachionaspis litoralis Ferris, revived combination; Duplachionaspis mackenziei McDaniel, revived combination; Duplachionaspis milleri (Howell), new combination; Duplachionaspis nakaharai (Howell), new combination; Duplachionaspis peninsularis (Howell), new combination; Duplachionaspis spartinae (Comstock), revived combination; Duplachionaspis texana (Liu & Howell) new combination; Duplachionaspis uniolae (Takagi), new combination; Duplachionaspis mutica (Williams) (from Aloaspis Williams), new combination; Epidiaspis doumtsopi (Schneider), new combination (from Diaspis Costa); Fiorinia ficicola (Takahashi), new combination (from Ichthyaspis Takagi); Fiorinia macroprocta (Leonardi), revived combination (this and the next 2 species of Fiorinia Targioni Tozzetti all from Trullifiorinia Leonardi); Fiorinia rubrolineata Leonardi, revived combination; Fiorinia scrobicularum Green, revived combination; Genaparlatoria pseudaspidiotus (Lindinger), revived combination (from Parlatoria); Greeniella acaciae (Froggatt), new combination (this and the next 4 Greeniella Cockerell species all from Gymnaspis Newstead); Greeniella cassida (Hall & Williams), new combination; Greeniella grandis (Green), new combination; Greeniella perpusilla (Maskell), new combination; Greeniella serrata (Froggatt), new combination; Hendersonaspis anomala (Green), new combination (from Ancepaspis); Hulaspis bulba (Munting), new combination (this and the next Hulaspis Hall species both from Andaspis MacGillivray); Hulaspis formicarum (Ben-Dov), new combination; Lepidosaphes antidesmae (Rao in Rao & Ferris), new combination (this and the next 19 species all from Andaspis); Lepidosaphes arcana (Matile-Ferrero), new combination; Lepidosaphes betulae (Borchsenius), new combination; Lepidosaphes citricola (Young & Hu), new combination; Lepidosaphes conocarpi (Takagi), new combination; Lepidosaphes crawi (Cockerell), revived combination; Lepidosaphes erythrinae Rutherford, revived combination; Lepidosaphes incisor Green, revived combination; Lepidosaphes indica (Borchsenius), new combination; Lepidosaphes kashicola Takahashi, revived combination; Lepidosaphes kazimiae (Williams), new combination; Lepidosaphes laurentina (Almeida), new combination; Lepidosaphes maai (Williams & Watson), new combination; Lepidosaphes mackieana McKenzie, revived combination; Lepidosaphes micropori (Borchsenius), new combination; Lepidosaphes punicae Laing, revived combination; Lepidosaphes quercicola (Borchsenius), new combination; Lepidosaphes recurrens (Takagi & Kawai), new combination; Lepidosaphes viticis (Takagi), new combination; Lepidosaphes xishuanbannae (Young & Hu), new combination; Lepidosaphes giffardi (Adachi & Fullaway), new combination (from Carulaspis MacGillivray); Lepidosaphes garciniae (Young & Hu), new combination (this and the next 2 species all from Ductofrontaspis Young & Hu); Lepidosaphes huangyangensis (Young & Hu), new combination; Lepidosaphes jingdongensis (Young & Hu), new combination; Lepidosaphes recurvata (Froggatt), revived combination (from Metandaspis Williams); Lepidosaphes ficicola Takahashi, revived combination (this and the next 2 species all from Ungulaspis MacGillivray); Lepidosaphes pinicolous Chen, revived combination; Lepidosaphes ungulata Green, revived combination; Lepidosaphes serrulata (Ganguli), new combination (from Velataspis Ferris); Lepidosaphes huyoung Normark, replacement name for Andaspis ficicola Young & Hu; Lepidosaphes tangi Normark, replacement name for Andaspis schimae Tang; Lepidosaphes yuanfeng Normark, replacement name for Andaspis keteleeriae Yuan & Feng; Leucaspis ilicitana (Gómez-Menor), new combination (from Aonidia); Lopholeucaspis spinomarginata (Green), new combination (from Gymnaspis); Melanaspis campylanthi (Lindinger), new combination (from Aonidia); Mohelnaspis bidens (Green), new combination (from Fiorinia); Parlatoria affinis (Ramakrishna Ayyar), new combination (this and the next 4 Parlatoria species all from Gymnaspis); Parlatoria ficus (Ramakrishna Ayyar), new combination; Parlatoria mangiferae (Ramakrishna Ayyar), new combination; Parlatoria ramakrishnai (Green), new combination; Parlatoria sclerosa (Munting), new combination; Parlatoria bullata (Green), new combination (from Bigymnaspis); Parlatoria leucaspis (Lindinger), new combination (this and the next species both from Cryptoparlatorea Lindinger); Parlatoria pini (Takahashi), new combination; Parlatoria tangi Normark, replacement name for Parlatoria pini Tang; Pseudoparlatoria bennetti (Williams), new combination (from Parlagena McKenzie); Pseudoparlatoria chinchonae (McKenzie), new combination (from Protodiaspis Cockerell); Pseudoparlatoria larreae (Leonardi), revived combination (from Protargionia Leonardi); Quernaspis lepineyi (Balachowsky), new combination (from Chionaspis); Rhizaspidiotus nullispinus (Munting), new combination (from Aonidia); Rolaspis marginalis (Leonardi), new combination (from Lepidosaphes); Salicicola lepelleyi (De Lotto), new combination (from Anotaspis Ferris); Tecaspis giffardi (Leonardi), new combination (from Dinaspis); Trullifiorinia geijeriae (Froggatt), new combination (from Fiorinia); Trullifiorinia nigra (Lindinger), new combination (from Crypthemichionaspis Lindinger); and Voraspis olivina (Leonardi), new combination (from Lepidosaphes).